A dependência latino-americana: o "desenvolvimento do subdesenvolvimento" à luz da teoria marxista da dependência - Silva, Adalberto Oliveira da (2011)
This work aims to recover the contributions of Marxist theory of dependence in the 1960s and 1970s in order to understand the dynamics of peripheral capitalism in Latin America. Ruy Mauro Marini and Theotonio dos Santos, as the main authors of this line of studies of dependence, seek in the analysis of the contradictions of the capitalist system the explanation for the dependent status of Latin American countries. Thus, the dependence would be seen as a conditioning situation attributed to the development of the central economies due to the underdevelopment of peripheral economies. This is due to the transfer of values produced in the periphery toward the center economies, which would lead within the economies dependent on the formation of "deformations", both in its production process and the cycle of capital that it presents. Focussing on the region's economic integration can be evidenced the reasons for the condition of dependence on the movement of capital accumulation in Latin America, highlighting the relevant factors in this case the characterization and the basis for examining the state of dependence in its various manifestations . Thus, besides the presentation of this theory, the waves of criticism will that sought to refute the explanations constructed by Marxist dependency theory be highlighted and at the same time, accompanied by their replies, generating a debate that has enriches the dialectics of dependence and the conclusions moving towards the development alternatives for the countries of Latin America